UJI ERROR METER PADA KWH METER PASCABAYAR 1 PHASA MEREK MELCOINDA DAN MEREK SANXING YANG DIGUNAKAN OLEH PT PLN (PERSERO) SEBAGAI ALAT UKUR PEMAKAIAN ENERGI LISTRIK - Handoyo, Nanda Restu; Tamaji (Seminar Nasional Ilmu Terapan, 2024)
PT Perusahaan Listrik Negara (Persero) or commonly abbreviated as PLN is an Indonesian state-owned company operating in the electricity sector, which has one mission, one of which is running the electricity business and other related fields, focusing on customer satisfaction, company members and shareholders. share. To make this happen, PT. PLN uses a tool called a kWhmeter to calculate the number of electrical ener-gy transactions that have been used by customers. Before a kWhmeter is installed on a customer's plot, the kWhmeter must first be tested meter error. If the test meter error reading test is not implemented, then there is a possibility that the kWhmeter will experience interference, causing inaccurate electrical energy measure-ments which can cause losses to the PT. PLN or the customer. The test meter error functions to find out the magnitude of the meter error value for each kWhmeter carried out in the PLN warehouse, if the test meter er-ror results are still within the class range, the kWhmeter is ready to be distributed to PLN customers. By im-plementing the test meter error, you can eliminate kWhmeter abnormalities caused by the product or manufac-turer making the kWhmeter. The test error meter also functions as a physical check for the kWhmeter to have no defects before it is installed on the customer's plot. The test meter error was implemented at PT. PLN (Persero) based on Directors Regulation (Perdir) 088-Z.P/DIR/2016 which is now Directors Regulation (Perdir) 0028.P/DIR/2023.